Erythematous ulcero-proliferative exophytic lesion in an oral squamous cell carcinoma patient- An unusual case of Trichosporonosis - Umamaheswari Kesavachandran; C Arun Kumar (Indian Journal of Pathology and Microbiology)
The emergence of non-Candida yeast infections in humans has been increasingly recognized over the last decades. Trichosporon is the third most isolated non-candidal yeast in patients with an impaired immune system. We report a rare case of Trichosporon asahii causing erythematous oral lesion in a patient with squamous cell carcinoma. Our case highlights the occurrence of unusual yeast pathogens in patients with cancer with typical clinical presentations and warrants suspicion of fungal etiology to prevent misdiagnosis of trichosporonosis.